Proceedings of the 6th Joint Conference on Lexical and Computational Semantics (*SEM 2017) 2017
DOI: 10.18653/v1/s17-1007
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Intensities in Tweets

Abstract: This paper examines the task of detecting intensity of emotion from text. We create the first datasets of tweets annotated for anger, fear, joy, and sadness intensities. We use a technique called best-worst scaling (BWS) that improves annotation consistency and obtains reliable fine-grained scores. We show that emotion-word hashtags often impact emotion intensity, usually conveying a more intense emotion. Finally, we create a benchmark regression system and conduct experiments to determine: which features are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(104 citation statements)
references
References 35 publications
2
82
0
2
Order By: Relevance
“…Whilst GPELs offer useful knowledge about emotion-rich words, they are static and are likely to have poor coverage of the emotion vocabulary used in domains like Twitter. For emotion classification of tweets, Mohammad [17] and [22] demonstrated that DSEL based features offer significant gains over n-grams when compared to those of GPEL based features [32]. However feature extraction using DSELs has not been explored beyond binary and integer counts.…”
Section: Features For Emotion Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Whilst GPELs offer useful knowledge about emotion-rich words, they are static and are likely to have poor coverage of the emotion vocabulary used in domains like Twitter. For emotion classification of tweets, Mohammad [17] and [22] demonstrated that DSEL based features offer significant gains over n-grams when compared to those of GPEL based features [32]. However feature extraction using DSELs has not been explored beyond binary and integer counts.…”
Section: Features For Emotion Classificationmentioning
confidence: 99%
“…Different learning methodologies such as Point-wise Mutual Information (PMI) [22], Latent Dirichlet Allocation (LDA) in a semi-supervised setting [35] have been applied to learn DSEls. In addition, supervised LDA (sLDA) [36] offers a more accurate means to model emotion classes as topics and for lexicon generation.…”
Section: Learning Emotion Lexiconsmentioning
confidence: 99%
See 3 more Smart Citations